Answer:
A. x = 3, y = 2
Explanation:
The hypotenuse and the length of one leg of one right triangle must be equal to the hypotenuse and corresponding length of the one leg of the other ∆ for both triangles to be equal by the HL Congruence Theorem.
Thus, let's find x and y by setting the corresponding lengths of the two right ∆s equal to each other.
Therefore:
x = y + 1 ----› eqn. 1
2x + 3 = 3y + 3 ----› eqn. 2
Substitute x = (y + 1) into eqn. 2, and solve for y.
2x + 3 = 3y + 3 ----› eqn. 2
2(y + 1) + 3 = 3y + 3
2y + 2 + 3 = 3y + 3
2y + 5 = 3y + 3
Collect like terms
2y - 3y = -5 + 3
-y = -2
Divide both sides by -1
y = 2
Substitute y = 2 into eqn. 1.
x = y + 1 ----› eqn. 1
x = 2 + 1
x = 3